(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the factors associated with accident prevention actions promoted by early childhood teachers. Method: Cross-sectional, quantitative study with 129 teachers working at the Municipal Centers for Early Childhood Education in Recife-PE. Data were collected between September / 2017 and June / 2018 through individual face-to-face interviews. Descriptive analysis and bivariate analysis were used using Pearson’s chi-square test and Fisher’s exact test, with a 95% confidence interval. Results: The actions were categorized into actions related to the physical structure / furniture of the institution (27.3%), the performance of the teacher (47.3%) and the stages of child development (25.4%). The age between 20 to 39 years (p = 0.027) and being married or having a stable relationship (p = 0.025) were associated with a greater number of preventive actions. Conclusion: Younger teachers who live with a partner promoted a greater number of preventive actions related to childhood accidents in the Early Childhood Education Centers.